2014
DOI: 10.1016/j.jacc.2014.02.530
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Deferred Stenting Versus Immediate Stenting to Prevent No- or Slow-Reflow in Acute ST-Segment Elevation Myocardial Infarction (DEFER-STEMI)

Abstract: ObjectivesThe aim of this study was to assess whether deferred stenting might reduce no-reflow and salvage myocardium in primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction (STEMI).BackgroundNo-reflow is associated with adverse outcomes in STEMI.MethodsThis was a prospective, single-center, randomized, controlled, proof-of-concept trial in reperfused STEMI patients with ≥1 risk factors for no-reflow. Randomization was to deferred stenting with an intention-to-stent 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
3
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(183 citation statements)
references
References 29 publications
7
162
3
11
Order By: Relevance
“…STEMI accounted for 39% (31,653 patients) of all hospital admissions due to myocardial infarction in the UK (excluding Scotland). 1 The unadjusted 30-day mortality rate for STEMI patients was 8.1% during the period 2013-14, compared with ABSTRACT ST elevation myocardial infarction 12.4% ten years earlier (2003)(2004));…”
Section: Incidence and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…STEMI accounted for 39% (31,653 patients) of all hospital admissions due to myocardial infarction in the UK (excluding Scotland). 1 The unadjusted 30-day mortality rate for STEMI patients was 8.1% during the period 2013-14, compared with ABSTRACT ST elevation myocardial infarction 12.4% ten years earlier (2003)(2004));…”
Section: Incidence and Pathophysiologymentioning
confidence: 99%
“…Other avenues showing early promise in STEMI include deferred compared with immediate stenting following reestablishment of flow in the culprit artery, 31 use of systemic hypothermia (COOL AMI pilot trial), 32 bone marrow-derived cell therapy (BAMI trial) 33 and ischaemic preconditioning. …”
Section: Ppci: Procedural Considerationsmentioning
confidence: 99%
“…7,9,10 A singlecenter proof-of-concept study reported a lower rate of angiographic no-reflow in patients treated with DS versus IS, but the population was limited to individuals with a high risk of no-reflow. 11 The MIMI trial was conducted to confirm whether delayed (24-48 hours) versus immediate stent implantation significantly reduced myocardial MVO as determined by cardiac magnetic resonance imaging (MRI), thus improving myocardial reperfusion in patients with acute STEMI undergoing primary PCI.…”
mentioning
confidence: 99%
“…All patients should proceed urgently to the catheterization laboratory, and flow may need to be restored with a wire or gentle predilatation with a balloon. If high burden of thrombus is seen, deferred stenting with an interim period of adjunctive antiplatelet/anti thrombotic therapy may be useful to reduce the thrombus load and minimize complications (such as no-reflow) at time of stenting [47,48].…”
Section: Deferred Stentingmentioning
confidence: 99%